Changes evaluated in soccer-specific power endurance either with or without a 10-week, in-season, intermittent, high-intensity training protocol - Siegler, J.; Gaskill, S.; Ruby, B. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this study was to evaluate changes in soccer-specific power endurance of 34 female high school soccer players throughout a season either with or without an intermittent, high-intensity exercise protocol. Thirty-four female high school soccer players were tested prior to the 2000 fall season and again 10 weeks later. The tests included an abridged 45-minute shuttle test (LIST), hydrostatic weighing, vertical jump, 20-m running-start sprint, and 30-second Wingate test. The experimental group (EG; n = 17, age 16.5 ± 0.9 years) completed a 10-week in-season plyometric, resistive training, and high-intensity anaerobic program. The control group (n = 17, age 16.3 ± 1.4 years) completed only traditional aerobic soccer conditioning. Statistical significance was set at < 0.05. The experimental group showed significant improvements in the LIST (EG = 394 seconds ± 124 seconds), 20-m sprint (EG = 0.10 seconds ± 0.10 seconds), increase in fat-free mass (EG = 1.14 kg ± 1.22 kg), and decreases in fat mass (EG = 1.40 kg ± 1.47 kg) comparing pre- to postseason. This study indicates that a strength and plyometric program improved power endurance and speed over aerobic training only. Soccer-specific power endurance training may improve match performance and decrease fatigue in young female soccer players.